Appraisal of geothermal potentials of some parts of the Abakaliki Anticlinorium and adjoining areas (Southeast Nigeria) using magnetic data - Eldosouky, Ahmed M.; Ekwok, Stephen E.; Ben, Ubong C.; Ulem, Christian A.; Abdelrahman, Kamal; Gomez-Ortiz, David; Akpan, Anthony E.; George, Anthony Michael; Pham, Luan Thanh (Frontiers in Earth Science, 2023)
The Abakaliki Anticlinorium and adjoining areas were appraised with the object of delineating high geothermal potential zones. Spectral depth analysis involving an improved centroid technique was used to analyze high-quality magnetic data. The obtained geothermal parameters were gridded to map the various geothermal features within the investigated area. The obtained results varied from 4. 99-9.35 km, 2.31-6.15 km, 6.11-16.28 km, 35.63-94.93 °C/km, and 89.07-237.32 mW/m 2 for centroid depth, top depth, Curie point depth, geothermal gradient, and heat flow values varied, respectively. The delineated semi-oval structure in the central zone of the investigated region characterized by shallow Curie point depth (CPD) (<8.5 km) correlates with the location of high heat flow (HF) (>191.0 mW/m 2 ) and geothermal gradient (GG) (>74.0 °C/km) region. The high geothermal potential of the region is triggered by the massive post-rift tectonic event of the Santonian period related to the Abakaliki Anticlinorium. Further geophysical exploration programs should be carried out before exploitation activities at anomalous geothermal regions.